From here to you - McGuire, Jamie (McGuire, Jamie. Crash and burn., 2018)
As Darby Dixon sits in a tiny Texas church bathroom on her wedding day holding a positive pregnancy test, she realizes that marrying her fiancé would be the worst decision of her life. With very little cash and a ton of courage, she flees town to take a new name and start a new life. Ex-Marine Scott "Trex" Trexler worked in the most treacherous, corrupt, war-torn places on earth. With his new top-secret security job, he finally has a chance to return to the one place he's felt at peace: Colorado Springs, Colorado. When he checks into a hotel, he may want the cute clerk to think he's another hotshot firefighter battling the nearby mountain blaze, but Darby's ex is getting closer to finding her. And sometimes what you don't know can hurt you.